Sex determination in malaria parasites. - Paul, R; Coulson, T; Raibaud, A; Brey, P (2000)
A century ago, W. G. MacCallum identified distinct male and female forms in malaria parasites of both birds and humans. Since then, scientists have been puzzled by the high female-to-male ratios of parasites in Plasmodium infections and by the mechanism of sex determination. The sex ratio of malaria parasites was shown to become progressively more male as conditions that allow motility and subsequent fertilization by the male parasites become adverse. This resulted from an increased immune response against male gametes, which coincides with intense host erythropoietic activity. Natural and artificial induction of erythropoiesis in vertebrate hosts provoked a shift toward male parasite production. This change in parasite sex ratio led to reduced reproductive success in the parasite, which suggests that sex determination is adaptive and is regulated by the hematologic state of the host.